Diagnóstico de prevalencia de tuberculosis Mycobacterium spp. en bovinos de explotación bajo filiación de la Asociación de Ganaderos del cantón Bolívar - Sabando Vera, Luis Ángel (2023)
The present investigation was developed in nine farms of the members of the Association of Cattlemen in Bolívar canton, Manabí province; with the purpose of diagnosing the prevalence of tuberculosis Mycobacterium spp. in farm cattle, using the tuberculin skin technique. To carry out this study, the presence of tuberculosis was determined by means of the preliminary tuberculin test, applied to 219 bovines; they were selected under the criteria of low body condition and for having greater contact with human beings. Subsequently, the confirmation of the positive cases to tuberculosis was carried out, through the delayed hypersensitivity test with the Comparative Cervical Tuberculinization method. From the results it was obtained that 23 positive cases were determined, which is equivalent to 10.50% of tuberculosis of the total number of animals intervened by applying the Tuberculin skin test. These cases were re-inoculated with avian tuberculin 180 days after the first test was applied, in order to verify their positivity. From this process, 3 positive cases were obtained, which represents a prevalence of tuberculosis of 1.37% of the 219 bovines sampled from the evaluated livestock farms. Finally, the results obtained from the diagnosis of tuberculosis in the cattle farms under the affiliation of the Association of Cattlemen in Bolívar canton, in the presence of the representatives of the farms under study and the authorities at ESPAM MFL.